Controllable Synthesis of Porphyrin‐Based 2D Lanthanide Metal–Organic Frameworks with Thickness‐ and Metal‐Node‐Dependent Photocatalytic Performance. Issue 8 (16th January 2020) - Jiang, Zhong Wei; Zou, Yang Chun; Zhao, Ting Ting; Zhen, Shu Jun; Li, Yuan Fang; Huang, Cheng Zhi
Abstract: Synthesizing 2D metal–organic frameworks (2D MOFs) in high yields and rational tailoring of the properties in a predictable manner for specific applications is extremely challenging. Now, a series of porphyrin‐based 2D lanthanide MOFs (Ln‐TCPP, Ln=Ce, Sm, Eu, Tb, Yb, TCPP=tetrakis(4‐carboxyphenyl) porphyrin) with different thickness were successfully prepared in a household microwave oven. The as‐prepared 2D Ln‐TCPP nanosheets showed thickness‐dependent photocatalytic performances towards photooxidation of 1, 5‐dihydroxynaphthalene (1, 5‐DHN) to synthesize juglone. Particularly, the Yb‐TCPP displayed outstanding photodynamic activity to generate O2 − and 1 O2 . This work not only provides fundamental insights into structure designing and property tailoring of 2D MOFs nanosheets, but also pave a new way to improve the photocatalytic performance. Abstract : Through thick and thin : A series of porphyrin‐based 2D lanthanide MOFs of different thickness are successfully synthesized through a microwave‐assisted route. The photocatalytic activity of as‐prepared nanosheets can be effectively regulated by the thickness and by the metal nodes.